Risks of Online Health Information Seeking: Adaptation of the OHISS in the Russian Sample - A.A. Maksimenko; A.A. Zolotareva (Клиническая и специальная психология)
The development of the Internet, along with the improvement of patients’ digital skills, makes them competent in some matters of medical care. The aim of this study was to adapt the Online Health Information Seeking Scale in the Russian-speaking sample with the establishment of relationships with such cyber phenomena as doomscrolling, cyberchondria, and social media addiction. In an all-Russian online survey conducted using the service Toloka.AI, 1,025 people took part. The toolkit included the following questionnaires: the Online Health Information Seeking Scale (OHISS), the Doomscrolling Scale (DS), the Cyberchondria Severity Scale (CSS), the Bergen Social Media Addiction Scale (BSMAS). The results showed that the Russian version of the OHISS has a one-factor structure and high internal consistency (Cronbach’s α = 0.845; Mc’Donald’s ω = 0.847). The OHISS scores were statistically significantly positively correlated with scores of doomscrolling, cyberchondria, and social media addiction. The online health information seeking was not related to the age of the respondents, their income level and education level. Women, respondents who are married and separated, and respondents who consider themselves to be quite religious were exposed to more frequent online searches for health information. Empirical data obtained using the Online Health Information Seeking Scale allow us to consider the adapted scale as a psychometrically sound diagnostic instrument and recommend it for solving practical and research tasks.